PENGARUH PEMBERIAN PUPUK ORGANIK PADAT KOTORAN KAMBING TERHADAP KUALITAS NUTRISI HIJAUAN SORGUM (BICOLOR L. MOENCH): PENGARUH PEMBERIAN PUPUK ORGANIK PADAT KOTORAN KAMBING TERHADAP KUALITAS NUTRISI HIJAUAN SORGUM (BICOLOR L. MOENCH) - Jefrianus Banggur; I Nyoman Kaca; Luh Suariani (GEMA AGRO, 2026)
Success in developing a livestock business is greatly influenced by three key elements, namely the availability, quality, and continuity of animal feed supply. In general, ruminant livestock feed consists of green fodder and concentrates. Concentrates are generally formulated from waste and by-products of the agricultural and agro- industrial sectors. The supply of green fodder, especially grass, often fluctuates in terms of both quantity and quality, especially during the dry season, due to limited water and decreased plant growth rates. This condition requires alternative green fodder that is adaptive to marginal environments, has high biomass productivity, and adequate nutritional value. One of the plants with great potential is sorghum (Sorghum bicolor L. Moench), Sorghum (Sorghum bicolor (L.) Moench) is a cereal crop with great potential to be developed as green fodder. In order to meet nutrient needs, the appropriate fertilization is by providing solid organic fertilizer from goat manure. This study aims to determine the nutritional content of Sorghum (Sorghum bicolor L. Moench) green fodder given solid organic fertilizer from goat manure. This research was conducted from September to December 2025 at Jln. Sedap Malam, Banjar Kebon Kori Kelod, Gang Melati No. 15, East Denpasar. This research used a Randomized Block Design (RBD) with 5 treatments and 3 replications. The treatment used was with different fertilization doses P0 = Sorghum plants without giving solid organic fertilizer goat manure (Control), P1 = Sorghum plants with a fertilization dose of solid organic fertilizer goat manure 7.5 tons / ha, P2 = sorghum plants with a fertilization dose of solid organic fertilizer goat manure 15 tons / ha, P3 = sorghum plants with a fertilization dose of solid organic fertilizer goat manure 22.5 tons / ha, P4 = sorghum plants with a fertilization dose of solid organic fertilizer goat manure 30 tons / ha Based on statistical analysis, it was found that the effect of giving solid organic fertilizer goat manure on the nutritional quality of sorghum plants (Sorghum bicolor L. Moench) showed no significant effect (P.> 0.05) on dry matter and ash content variables. While the variables of crude protein, crude fiber, and crude fat showed very significant results. (P. <0.01). The results of the study showed that solid organic fertilizer goat manure was able to improve the nutritional quality of sorghum plants. These results indicate that the research conducted was positively correlated. Further research is needed to determine the optimal dosage of solid organic fertilizer. The best dosage is 22.5 tons/ha.